José de Alencar e o teatro: Um romântico realista - Reis, Douglas Ricardo Hermínio [UNESP] (Universidade Estadual de Maringa, 2013)
José de Alencar (1829-1877) is more known by the public reader by his novels. However, Alencar was also one of the most famous Brazilian playwright of nineteenth century's second half, with a work marked by successes, failures and controversies. This article intends to study an important part of his work, especially the beginning of his actions towards the still incipient Brazilian theatre in his chronic Ao correr da pena, as well as the analysis of two plays, O demônio familiar (1857), and As asas de um anjo (1857). These works not only show his public's success and failure, but also his flair for controversy. By using as theoretical basis João Roberto Faria and Martin Esslin, as well as other literary and theatre theorists, it will be shown that, although he defended French realism in theatre and used proceedings related to the genre, such realism, on his plays, was mixed with romantic solutions what made his work unique.
José de Alencar and the theater: A romantic realist
Keywords: Brasilian theatre; French realism; José de Alencar; Romanticism